Study on the Production of Cellulase by Using Aspergillus Oryzae and its Application on the Green Coffee Treatment - Nguyen, Quang Duy; Lam, Duc Thinh; Nguyen, Van Hoang; Dinh, Yen Nhi; Le, Hong Phu (Journal of Technical Education Science, 2022)
The objective of this study was to investigate the production of microbial cellulase by using Aspergillus oryzae and its application in the treatment of coffee. The cellulase producing method used for microbe medium was in submerged fermentation with malt extract medium. The method used for determining the cellulase activity was spectrophotometry at the wavelength 540 nm with 3,5-DNS reagent to measure the production of reducing sugar (the product of enzymatic reaction). Then, cellulase was applied on green Robusta coffee bean to enhance the extraction of total soluble solids. The result showed that at 6% (v/w) cellulase and 50°C of enzyme treatment, lasting for 24 hours, the extraction of soluble solids was highest at 4.47±0.06°Brix. The efficiency of extraction improved 21.79% compared to the control. This result could be applied in the production of coffee to improve the quality of coffee products.